Increased ShTAL1 IgE responses post-Praziquantel treatment may be associated with a reduced risk to re-infection in a Ghanaian S. haematobium-endemic community - Elias K. Asuming-Brempong; Irene Ayi; William van der Puije; Ben A. Gyan; Irene A. Larbi; Yvonne Ashong; Naa Adjeley Frempong; Joseph K. Quartey; Joseph Otchere; Frances M. Jones; Shona Wilson; David W. Dunne; et al. (Public Library of Science (PLoS), 2022)
Background Evidence from recent studies in Schistosoma mansoni-endemic areas show an age-associated immunity that is positively correlated with IgE titres to Schistosoma mansoni-specific tegumental allergen-like protein 1 (SmTAL1). The structural homology between SmTAL1 and the S. haematobium-specific TAL1 (ShTAL1) has been verified, yet it remains unclear whether similar age- and immune-associated trends characterize ShTAL1. This community-based intervention study was conducted to assess whether ShTAL1IgE responses post-treatment with praziquantel (PZQ) might be associated with a reduced risk to re-infection with S. haematobium. Methodology/Principal findings This study was conducted at Agona Abodom, Central Region, Ghana, and involved 114 participants aged 6 to 55 years. EDTA blood samples were collected at baseline and 7 weeks after PZQ treatment (Follow-up). Baseline and Follow-up titres of specific IgG1, IgG4, and IgE antibodies to the S. haematobium-specific adult worm antigen (ShAWA), the Sh-specific soluble egg antigen (ShSEA), and the Sh-specific tegumental-allergen-like 1 protein (ShTAL1) in plasma samples were measured using sandwich ELISA. Participants at both time points also provided stool and urine for helminth egg detection by microscopy. Prevalence of S. haematobium at baseline was 22.80%, and decreased to 3.50% at Follow-up. The egg reduction rate (ERR) was 99.87%. Overall plasma levels of ShTAL1-IgE increased 7 weeks post-PZQ treatment, and with increasing age; whiles S. haematobium infection prevalence and intensity decreased. For S. haematobium-infected participants who were egg-negative at Follow-up (N = 23), minimal median levels of ShTAL1-IgE were observed for all age groups prior to treatment, whilst median levels increased considerably among participants aged 12 years and older at Follow-up; and remained minimal among participants aged 11 years or less. In the univariate analysis, being aged 12 years or older implied an increased likelihood for ShTAL1-IgE positivity [12-14 years (cOR = 9.64, 95% CI = 2.09-44.51; p = 0.004); 15+ years (cOR = 14.26, 95% CI = 3.10-65.51; p = 0.001)], and this remained significant after adjusting for confounders [12-14 years (aOR = 22.34, 95% CI = 2.77-180.14; p = 0.004); ≥15 years (aOR = 51.82, 95% CI = 6.44-417.17; p < 0.001)]. Conversely, median ShTAL1-IgG4 titres were hardly detectible at Follow-up. Conclusions/Significance These findings demonstrate that increased IgE levels to ShTAL1 7 weeks after PZQ treatment could be associated with a reduced risk to re-infection, and adds to the large body of evidence suggesting a protective role of the treatment-induced ShTAL1 antigen in schistosomiasis infections. It was also quite clear from this work that apart from being persistently S. haematobium-positive, elevated ShTAL1-IgG4 levels at Follow-up could be indicative of susceptibility to re-infection. These outcomes have important implications in vaccine development, and in shifting the paradigm in mass chemotherapy programmes from a 'one-size-fits-all' approach to more sub-group-/participant-specific strategies in endemic areas. Author summary The current World Health Organization (WHO)-approved strategy for combating schistosomiasis, is the administration of praziquantel (PZQ) to subjects living in endemic communities. Due to concerns of the potential development of resistance to PZQ, there have been extensive studies to find putative candidate antigens capable of eliciting protective immunity particularly against the schistosomulum. One of such family of antigens discovered is the Schistosoma mansoni tegumental allergen-like proteins 1 through 13 (SmTAL1-13), of which the first six have been extensively studied. Although not present in the 3-hour schistosomulum, the SmTAL1 antigen has been found to induce cross-reactive IgEs that also recognize the SmTAL3 and SmTAL5 antigens present on the surface of cercariae and schistosomulae. Various epidemiological studies have indicated IgEs induced by SmTAL1 as potentially good markers/indicators for developing resistance to infection/re-infection. In this community-based intervention study, we sought to determine whether outcomes realized for Schistosoma haematobium TAL1 IgE. 7 weeks-post PZQ treatment would be predictive of protection against re-infection with S. haematobium. Our work not only assesses immune responses associated with ShTAL1, but also explores immune profiles that may characterize participants susceptible or resistant to re-infection with S. haematobium.